Endodermal sinus tumor with pancreatic origin: A case report. (December 2022) - Zahid, Muhammad Jawad; Hussain, Musarrat; Zeb, Muhammad; Haseeb, Abdul; Khan, Hira Bakhtiyar
Abstract: Endodermal Sinus tumor is a rare malignant type of germ cell tumor (GCT). Primary endodermal sinus tumor, especially in the head of pancreas, is extremely rare. The case under consideration is of a 22 year old male who presented with pancreatic mass causing postprandial nausea and vomiting, and raised AFP levels. The biopsy of the mass revealed the endodermal sinus tumor, and the pancreatic origin was confirmed by a CT scan and a negative scrotal ultrasound. As the tumor was unresectable initially, a gastrojejunostomy was done to relieve the obstructive symptoms. Whipple procedure was performed two months after 4 cycles of BEP chemotherapy to remove the residual tumor in pancreas. It is crucial to highlight this uncommon case in order to increase surgeons' and oncologists' knowledge of the malignant extra-gonadal GCTs diagnosis and treatment. Highlights: Primary Pancreatic Endoderm Sinus tumor (EST) is an extremely rare and very malignant form of germ cell tumor When resectable, tumor excision with tumor free margins and post-operative chemotherapy with PEB is the treatment of choice EST is very highly responsive to chemotherapy and can be used alone in an unresectable tumor Moderately high AFP levels should not rule out the diagnosis of EST EUS-FNA is a gold standard for confirmation of a pancreatic tumor